FDI and Economic Growth — Does the Quality of Banking Development Matter? - Nor Hakimah Haji Mohd; Soo-Wah Low; Abu Hassan Shaari Md Nor; Noor A. Ghazali (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2013)
This study examines the role of banking development quality in the FDI-growth nexus from 1998 to 2009. Banking development quality is measured using two standardized intermediation cost indicators and an index of banking development quality that is constructed based on the following indicators: overhead costs to total assets and net interest margin. The results for developed countries show that, on its own, FDI is negatively related to economic growth. However, when FDI is interacted with a banking development quality index, the quality of banking development is found to play a positive role in influencing the effects of FDI on economic growth. This suggests that the quality of banking development serves as an absorptive capacity that allows developed countries to benefit from the positive growth effects of FDI. On the contrary, for emerging countries, the findings indicate that banking development quality plays no role in influencing the impact of FDI on economic growth. This implies that the quality of banking development in emerging countries has yet to reach a level that allows it to importantly influence the growth effects of FDI.